*(a ± b)*

^{2}= a^{2}± 2ab + b^{2}*a*

^{2}- b^{2}= (a - b)(a + b)

**~~~~~~~~~~~~~~~**x + 5 x - 5

-------- − -------- =

x - 5 x + 5

LCD of (x - 5) and (x + 5) is (x - 5)(x + 5)

(x + 5)(x + 5) (x - 5)(x - 5)

----------------- − ---------------- =

(x - 5)(x + 5) (x - 5)(x + 5)

(x + 5)

^{2}− (x - 5)

^{2}

------------------------ =

x

^{2}- 5

^{2}

x

^{2}+ 10x + 25 − (x

^{2}- 10x + 25)

--------------------------------------- =

x

^{2}- 25

x

^{2}+ 10x + 25 - x

^{2}+ 10x - 25

------------------------------------ =

x

^{2}- 25

after combine like terms in numerator:

20x

-------- =

x

^{2}- 25

**20x**

**---------------- .**

**(x + 5)(x - 5)**

## Comments